No one knows - Ellison, J. T. (Gallery Books, 2016)
"In an obsessive mystery as thrilling as The Girl on the Train and The Husband's Secret, the New York Times bestselling coauthor of the Nicholas Drummond series will make you question every twist in her page turning novel and wonder which of her vividly drawn characters you should trust. The day Aubrey Hamilton's husband is declared dead by the state of Tennessee should bring closure so she can move on with her life. But Aubrey doesn't want to move on. She just wants Josh back. It's been five years since he disappeared, since their blissfully happy marriage they were happy, weren't they? screeched to a halt and Aubrey became the prime suspect in his disappearance. Five years of emptiness, solitude, loneliness, questions. Why didn't Josh show up at his friend's bachelor party? Who anonymously sent Aubrey her favorite cocktail at the bar where Josh stood her up? Was he murdered? Did he run away? And now, all this time later, who is the mysterious and strangely familiar figure suddenly haunting her new life? As her heroine faces the possibility that everything she thinks she knows about herself, her marriage, and her husband is a lie, New York Times bestselling author J.T. Ellison expertly peels back the layers of a complex woman who is hiding dark secrets beneath her unassuming exterior. In a masterful thriller for readers who love Gillian Flynn, Liane Moriarty, and Paula Hawkins, Ellison pulls you into a you'll never-guess merry-go-round of danger and deception. Round and round and round it goes, where it stops no one knows"--